The Impact of Financial Statement Disclosure on Conservatism in Financial Reporting: Evidence from Vietnam - Le, Tuan Bach (International Journal of Economics and Financial Issues, 2016)
The aim of this paper is to test the impact of financial statement disclosure on conservatism in Vietnamese financial statements. I use inter-earning announcement period returns and fiscal year returns to serve as economic news reflected in earnings during the financial statement disclosure period and prior to the financial statement disclosure period. I test conservatism in financial reporting of Vietnamese listed non-financial firms over the period of 2005 to 2015 using the two returns measures in succession. I find that conservatism principle is only ensured within the audited financial statement disclosure period. The findings have implications for our understanding of the role of auditors as well as rules and regulations of financial statement disclosure in improving the quality of accounting information. Keywords: Accounting, Accounting Information, Financial Reporting JEL Classifications: M40, M48